2014
DOI: 10.1109/led.2014.2336795
|View full text |Cite
|
Sign up to set email alerts
|

A Near-Infrared Range Photodetector Based on Indium Nitride Nanocrystals Obtained Through Laser Ablation

Abstract: Cataloged from PDF version of article.We present a proof-of-concept photodetector that is sensitive in the near-infrared (NIR) range based on InN nanocrystals. Indium nitride nanocrystals (InN-NCs) are obtained through laser ablation of a high pressure chemical vapor deposition grown indium nitride thin film and are used as optically active absorption region. InN-NCs are sandwiched between thin insulating films to reduce the electrical leakage current. Under -1 V applied bias, the recorded photoresponsivity va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Thus, smaller InN-NCs were obtained by using lower laser energy in ablation procedure. In a previous study, we showed that the lower pulse energies with nanosecond laser ablation of InN thin film led to a decrease in the nanoparticle size distribution but the smaller nanoparticles were obtained with larger energies [22]. The target material has a great importance since the laser pulse with higher energy result in much more ablation process on the solid target while the increase in the energy did not affect the nanoparticle sizes after a certain value with the continuously stirred sample powder sample.…”
Section: Effects Of Laser Energy and Ablation Duration On Inn-ncsmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, smaller InN-NCs were obtained by using lower laser energy in ablation procedure. In a previous study, we showed that the lower pulse energies with nanosecond laser ablation of InN thin film led to a decrease in the nanoparticle size distribution but the smaller nanoparticles were obtained with larger energies [22]. The target material has a great importance since the laser pulse with higher energy result in much more ablation process on the solid target while the increase in the energy did not affect the nanoparticle sizes after a certain value with the continuously stirred sample powder sample.…”
Section: Effects Of Laser Energy and Ablation Duration On Inn-ncsmentioning
confidence: 91%
“…The average diameter of the produced InN-NCs was 10 nm [18]. These InN-NCs were shown to have applications such as a near infrared range photodetector [22] and charge trapping memory cells [23]. However, the starting material was HPCVD-grown InN thin film and the starting material, either a bulk target or a suspension, affects the final nanoparticle size in PLAL.…”
Section: Introductionmentioning
confidence: 99%
“…They also have a low band-gap energy, which is in the range of 0.7-0.9 eV, and they have unique electronic features such as high electron mobility, which allows fabricating high speed and high frequency electronic devices [76]. A near-infrared ranged photodetector has been demonstrated by using InN-NCs [77]. InN-NCs are generated by PLAL method from Laser Ablation -From Fundamentals to Applications 158 chemical vapor-deposited thin film.…”
Section: A Near-infrared Range Photodetector Based On Indium Nitride mentioning
confidence: 99%
“…(a) TEM image of InN-NCs, (b) schematic of photodetector, and (c) photosensitivity versus wavelength graph[77].…”
mentioning
confidence: 99%
“…III-V semiconductor nitrides, such as GaN, InN, and AlN, are extensively studied for their applications in electronics and optoelectronics. Among these nitrides, Indium nitride (InN) has the smallest bandgap (~0.7 eV), which makes it potentially interesting for solar cells and infrared detectors [1,2,[6][7][8]. Moreover, theoretical mobility of electrons at room temperature can be as high as 14000 cm 2 /V⋅s in InN [3], which is order of magnitude larger than that of GaN (1000 cm 2 /V⋅s) [4].…”
Section: Introductionmentioning
confidence: 99%